Implementasi Sistem Administrasi dan Forecasting Hasil Getah Karet Menggunakan Metode Moving Average - Trianggono, Muhamad Ibnu; Wahyudi, Jusuf; Jumadi, Juju (MEANS (Media Informasi Analisa dan Sistem), 2021)
One of the plantation companies is located in north bengkulu and there are two gardens, precisely in Air Sebayur Village, Pinang Raya District and the other one is in Gembung Raya Village, Napal Putih District. Data from the results of the rubber sap in the division is still recorded manually, namely handwriting and then processed using the office application package, namelymicrosoft excel. However, the data is only limited to the results of rubber latex for PT. Julang Oca Permana and was not reviewed for information in the data. Implementation of the administration system and forecasting of rubber latex results using the Moving Average method at PT. Julang Oca Permana (jop) Bengkulu Utara was created using the visual basic .net programming language. With the development of the application, it can be used as an alternative in predicting the amount of production of rubber latex every day based on trend data for the previous 3 days. Administration system and forecasting of rubber latex results using the Moving Average method at PT. Julang Oca Permana (jop) Bengkulu Utara, there are several menus that can be accessed in order to manage production data and predict the amount of production. Based on the tests that have been carried out, it can be concluded that the application is able to predict the number of production results of each division for the next day based on trend data from the previous 3 days.